2018
DOI: 10.1007/s10549-018-4726-x
|View full text |Cite
|
Sign up to set email alerts
|

Screening of over 1000 Indian patients with breast and/or ovarian cancer with a multi-gene panel: prevalence of BRCA1/2 and non-BRCA mutations

Abstract: In India, socioeconomic inequality limiting access to treatment is a major factor towards increased cancer burden; therefore, incorporation of a cost-effective and comprehensive multi-gene test will be helpful in ensuring widespread implementation of genetic screening in the clinical practice for hereditary breast and/or ovarian cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
60
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(79 citation statements)
references
References 29 publications
11
60
6
Order By: Relevance
“…and BRCA2 mutations in a cohort of Nigerian patients with breast cancer, and mutation rates as high as 25% are reported in patients with breast and ovarian cancer in India. 7,8 These rates are comparable to the BRCA1 and BRCA2 mutation rates initially characterized in patients of Ashkenazi ancestry with breast cancer. Large biobanking studies of unselected general populations are also finding higher frequencies of BRCA1 and BRCA2 mutations than expected.…”
supporting
confidence: 56%
“…and BRCA2 mutations in a cohort of Nigerian patients with breast cancer, and mutation rates as high as 25% are reported in patients with breast and ovarian cancer in India. 7,8 These rates are comparable to the BRCA1 and BRCA2 mutation rates initially characterized in patients of Ashkenazi ancestry with breast cancer. Large biobanking studies of unselected general populations are also finding higher frequencies of BRCA1 and BRCA2 mutations than expected.…”
supporting
confidence: 56%
“…Second, the present study population did not include a sufficient sample of histological subtypes other than HGSC; this limitation impairs the ability to capture the mutational landscape of these tumors. Third, as reported previously (58)(59)(60)(61). a multigene panel for germline and/or somatic testing would probably be cost effective, providing a substantial rate of clinically actionable pathogenic variants (62).…”
Section: Discussionmentioning
confidence: 74%
“…The comparison aimed to determine the similarities and differences between Chinese and the non‐Chinese Asian populations; Indian population: India has the 2nd largest population in the world, with highly diversified genetic background. Several large‐scale BRCA studies were reported recently with substantial BRCA data collected from the Indian patients . The comparison aimed to determine the similarities and differences between Chinese and Indian populations, the two largest populations in the world.…”
Section: Resultsmentioning
confidence: 99%
“…This variant had the highest prevalence of 5.6% (15 out of 266 detected by five studies). It is a stop-gain pathogenic mutation, present in the BIC, BMD, LOVD, ClinVar, BED databases and was reported as a Chinese founder mutation by a previous study (31 (2 out of 99), is pathogenic, and is present in the BMD, ClinVar, BED and LOVD databases.…”
Section: Comparison In Founder Mutationsmentioning
confidence: 96%
See 1 more Smart Citation